Effect of film thickness in gelatin hybrid gels for artificial olfaction - Esteves, Carina (2022)
Pest-OE/AGR/UI0245/2013 SCENT-ERC-2014-STG-639123 CapTherPV-ERC-2014-CoG-647596 POCI-01-0145-FEDER-007728